KESIAPAN LABORATORIUM TERPADU JURUSAN PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS NEGERI SEMARANG UNTUK E-LEARNING - Isa Ansori; Trimurtini Trimurtini; Elok Fariha Sari; Florentina Widihastrin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
Laboratory utilization is very important to support learning. The laboratory is very useful for measuring the standards of scienceand theory. Theoretical learning and practicum in the laboratory are integral activities in the teaching and learning process.This study aims to describe and find a laboratory readiness solution for the Department of Primary School Teacher Education,Faculty of Education, Semarang State University which supports the implementation of e-learning. The research variables werethe completeness of laboratory facilities, laboratory governance system of the Department of Primary School Teacher Education,lecturer and technical management, and users of the Laboratory of Primary School Teacher Education Study Program. Thesubjects of this study were lecturers, students of the Department of Primary School Teacher Education. Data items throughquestionnaires, observation, interviews, and documentation. Data were analyzed using qualitative descriptive. The resultsshowed the level of satisfaction of students and lecturers as laboratory users. This also illustrates the problems that often occurin managing laboratories of the Department of Primary School Teacher Education. Integrated laboratories at the Department ofPGSD FIP Semarang State University have a dual role in the fields of education, research and community service, although thethree are still in a sufficient category. Integrated laboratory management requires special management that is different fromlaboratory management in the field of study